NUMERICAL STUDY OF THE EFFECT OF INLET CONFIGURATION AND TANK ORIENTATION ON STRATIFICATION IN A THERMAL ENERGY STORAGE SYSTEM (Journal of Mathematics Mechanics and Computer Science, 2026)
Thermal energy storage (TES) is a technology that is well established in the solar energy sector, district heating and industrial waste heat recovery. The efficiency of these systems is mostly dependent on the quality of the thermal stratification — the maintenance of a stable temperature difference between the warm and cold section of the tank. Computational fluid dynamics (CFD) techniques are employed to analyze the effects of the inlet configuration and the tank orientation on the charging process of a TES system in this work. A cylindrical tank with height of 1.1 m and inner diameter of 0.46 m is considered with 13 tubes inside the tank to be used in the future for the integration of phase change material (PCM). There are two forms of inlet configuration compared, a distributed shower type inlet and concentrated single orifice, for both vertical and horizontal tank orientations. The numerical model is based on the three-dimensional transient conservation equations for mass, momentum and energy with a variable density of the heat transfer fluid which is a function of temperature. Each configuration is analyzed by the following performance criteria: MIX number, stratification number, storage capacity ratio, and exergy efficiency. The results demonstrate that there is a significant increase in capacity ratio, around 88.5% and exergy efficiency above 88% for vertical configuration compared to horizontal configuration which is reduced to 75 77% and 67–69%, respectively. Shower type inlet produces greater stratification for the vertical orientation due to lesser momentum of the jet than the other inlet design, but it will not have a major impact when compared to tank orientation.
Keywords: thermal energy storage; thermal stratification; CFD; inlet configuration; tank orientation; exergy efficiency